2020
DOI: 10.1007/s00464-020-07792-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-year clinical experience with magnetic sphincter augmentation and laparoscopic fundoplication

Abstract: Background Magnetic sphincter augmentation (MSA) is a surgical intervention for gastroesophageal reflux disease (GERD) which has been evaluated in numerous studies and has shown beneficial effects. Long-term effectiveness data for MSA as well as laparoscopic fundoplication (LF) in patients with GERD are needed. Objective The objective of this study was to evaluate the 3-year outcomes for MSA and LF in patients with GERD. Methods This prospective, multi-center, observational registry study evaluated MSA and LF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Most recently, Bonavina et al reported a significant difference in excessive gas bloating and the ability to vomit between MSA and LF patients, specifically excessive gas bloating was reported in 10% of MSA patients, compared to 31% of LF patients, while 91% of MSA patients retained their ability to vomit if needed, compared to only 44.4% of LF patients. 42 Persistent dysphagia, the most feared complication after anti-reflux surgery did not occur in our cohort, neither in patients with acidic nor weakly acidic reflux, at time of follow-up. However, rarely difficulties swallowing with solids was reported by 16 out of 67 (24%) patients, while 8 out of 67 (12%) patients had occasional difficulties swallowing with solids.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Most recently, Bonavina et al reported a significant difference in excessive gas bloating and the ability to vomit between MSA and LF patients, specifically excessive gas bloating was reported in 10% of MSA patients, compared to 31% of LF patients, while 91% of MSA patients retained their ability to vomit if needed, compared to only 44.4% of LF patients. 42 Persistent dysphagia, the most feared complication after anti-reflux surgery did not occur in our cohort, neither in patients with acidic nor weakly acidic reflux, at time of follow-up. However, rarely difficulties swallowing with solids was reported by 16 out of 67 (24%) patients, while 8 out of 67 (12%) patients had occasional difficulties swallowing with solids.…”
Section: Discussionmentioning
confidence: 47%
“…41 Concerning postoperative pharmacotherapy, here we show that 88% (p = 0.0001) of the patients did not need to use PPIs anymore, which is also in concordance with previously published articles. 17,41,42 When comparing the improvement of the three most common symptoms (heartburn 93% vs. 95%, p = 0.615; regurgitations 94% vs. 95%, p = 0.723; and respiratory complaints 91% vs. 96%, p = 0.373), we found no difference between patients with preoperative weakly acidic and acidic reflux. Also, no significant difference was observed in the postoperative use of PPIs between patients with the two types of reflux (weakly acidic 7 vs. acid 18, p = 0.808).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…1− 3 Multiple studies have shown that these two anti-re ux procedures result in comparable postoperative GERD symptom control, rates of freedom from PPI and pH normalization. 1,4,5 MSA is a less invasive and more physiologic surgical option, it preserves the ability of patient to belch and has a lower rate of gas bloating. 6 Recent studies have encouraged use of MSA in patients with large sliding hiatal hernias.…”
Section: Introductionmentioning
confidence: 99%